An organocatalytic route to endo-vinylene carbonates from carbon dioxide-based exo-vinylene carbonates - Qiao, Chang; Engel, Philipp D.; Ziegenhagen, Levi A.; Rominger, Frank; Schäfer, Ansgar; Deglmann, Peter; Rudolf, Peter; Comba, Peter; Hashmi, A. Stephen K.; Schaub, Thomas (Advanced synthesis & catalysis, 2024)
An organocatalytic route has been developed for the isomerization of exo-vinylene carbonates (exo-VCs) to endo-vinylene carbonates (endo-VCs). The exo-VC starting material can easily be obtained from propargylic alcohols via cyclization with carbon dioxide. In this study, these exo-VCs are shown to isomerize to the thermodynamically more stable endo-VCs in the presence of an N-heterocyclic base and phenol. Density functional theory (DFT) studies were conducted to elucidate the mechanism, tackling difficulties of the description of charge separation steps. This isomerization process delivers an ample diversity of endo-VCs in good to excellent yields and chemoselectivities under mild reaction conditions.